2023
DOI: 10.1007/s11019-023-10169-5
|View full text |Cite
|
Sign up to set email alerts
|

Research ethics in practice: An analysis of ethical issues encountered in qualitative health research with mental health service users and relatives

Sarah Potthoff,
Christin Hempeler,
Jakov Gather
et al.

Abstract: The ethics review of qualitative health research poses various challenges that are due to a mismatch between the current practice of ethics review and the nature of qualitative methodology. The process of obtaining ethics approval for a study by a research ethics committee before the start of a research study has been described as “procedural ethics” and the identification and handling of ethical issues by researchers during the research process as “ethics in practice.” While some authors dispute and other aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…We selected the research instruments validity and reliability (Lehmann et al, 2023), appropriateness for the study population (Taherdoost, 2022), feasibility and practicality (McLeod, 2021). At the same time, conducting the research, we ensured that the use of research instruments meets the ethical standards and safeguards the rights of participants (Arellano et al, 2023;Potthoff et al, 2023). It is necessary to state that all the research instruments were selected to directly address these questions and designed with the items that reliably capture the participants' attitudes and beliefs on the problem.…”
Section: Instrumentsmentioning
confidence: 99%
“…We selected the research instruments validity and reliability (Lehmann et al, 2023), appropriateness for the study population (Taherdoost, 2022), feasibility and practicality (McLeod, 2021). At the same time, conducting the research, we ensured that the use of research instruments meets the ethical standards and safeguards the rights of participants (Arellano et al, 2023;Potthoff et al, 2023). It is necessary to state that all the research instruments were selected to directly address these questions and designed with the items that reliably capture the participants' attitudes and beliefs on the problem.…”
Section: Instrumentsmentioning
confidence: 99%
“…Still, other authors envisage a more positive role for RECs in the ethics review of qualitative health research. They have contended that the differences between quantitative and qualitative methods and the challenges inherent in the ethics review of qualitative health research have been overstated and that qualitative health research must be subject to ethics review by an independent research committee (Jennings, 2012; Potthoff et al, 2023; Wassenaar and Mamotte, 2012). These authors also proposed models that aim to address the identified challenges and increase the competence of RECs in the review of proposals that include qualitative methodologies.…”
Section: Introductionmentioning
confidence: 99%